The Diagnostic Value of Thermography in Oncology: Current Evidence and Future Perspectives - Bioły, Anna; Marcjasz, Piotr; Dryja, Patryk; Boczar, Agata; Buliszak, Agnieszka; Babczyńska, Monika (Quality in Sport, 2025)
Introduction and Purpose: Thermography – imaging heat patterns via infrared (IR) cameras – offers a noninvasive, radiation-free approach to detect the increased regional skin temperature associated with tumors’ hypermetabolism and angiogenesis [3]. This review examines the diagnostic potential of thermography in oncology, focusing on its role in early cancer detection and monitoring of treatment, and evaluates whether modern advancements address past concerns. Material and methods of research: A thorough literature review was performed using PubMed and Web of Science. Summary of Knowledge: Thermography detects infrared emission from the body’s surface to map temperature distribution [3]. Breast cancer was the first field to embrace thermography [2]. Pilot studies in dermatology show IR thermography can differentiate melanoma from benign lesions [7]. In cancer monitoring, thermography appears promising: e.g. thermal imaging of breast tumors during therapy [8]. However, limitations include dependence on tumor depth, confounding factors [3], and lack of standardized protocols leading to variable results across studies [5, 6]. Conclusions: Thermography offers a physiologic imaging perspective that, with further validation and refinement, could enhance early cancer detection and real-time monitoring in oncology practice, rather than replace existing gold-standard methods.